Water, our relative: trauma, healing and hydropolitics. (6th December 2018) - Bresnihan, Patrick
Abstract: In response to austerity-led reforms of the Irish water sector implemented in 2014, a broad-based, popular movement mobilized and ultimately forced a reversal of these reforms two years later. At least in the formal, public debates, the main contention centered on how water services should be financed and controlled. This is not unique to the Irish case. As campaigns across the world testify, debates over ownership, financing, control and ultimately access to water services are often at the heart of water politics. Without sidelining these important campaigns and movements, this paper calls for other ways of imagining and doing water politics that begin by paying greater attention to water and our complex, uneven, and damaged relations with it. The article draws on inputs and discussions that arose during the day-long 'Thinkery' that gave rise to this Special Issue (organized in June 2017 in the University College Cork), as well as ongoing research with rural Group Water Schemes (GWSs) in Ireland. The non-spectacular forms of activism practised by some GWSs invites a form of hydropolitics that doesn't shy away from the toxic legacies that accrete and materialize (unevenly) in different water bodies. Drawing on the important contributions of Chas Jewett in the 'Thinkery', the terms trauma and healing take on an important force for re-directing the energies, assumptions and intentions of more familiar forms of water politics.